COMMUNICATIVE LANGUAGE TEACHING, STUDENT MOTIVATION, AND COGNITIVE ATTITUDES: ANALYZING THE MODERATING ROLE OF LANGUAGE CONTACT - Hashed Mabkhot; Otabek Djurabaev (Fonseca, Journal of Communication, 2024)
This research examines how communicative language teaching (CLT) influences students’ motivation in language learning within the context of Saudi Arabian higher education. It further explores the role of the cognitive component of language attitude as both a direct predictor of motivation and a mediator in the relationship between CLT and motivation, with language contact profile as a moderating factor. The study was conducted with 244 students across various programs at educational institutes in Saudi Arabia. Data were collected using structured questionnaires, with measurement scales adapted from previous research. Partial Least Squares Structural Equation Modeling (PLSSEM) was employed to analyze the hypothesized relationships, ensuring robustness in handling the study’s complex model. Results indicated that CLT positively and significantly enhances students’ motivation. The cognitive component of language attitude directly predicts motivation and mediates the CLT-motivation link. Additionally, language contact profile moderates the relationship between CLT and motivation, suggesting that exposure to the target language outside class strengthens motivational effects. This study enriches the theoretical understanding of motivation in language learning by highlighting the cognitive and environmental factors that amplify CLT’s impact. Practical implications encourage educators to incorporate CLT and foster language contact opportunities to maximize student motivation in diverse learning contexts.